Out-of-Hospital Cardiac Arrest –Optimal Management - M. Frohlich, Georg; M Lyon, Richard; Sasson, Comilla; Crake, Tom; Whitbread, Mark; Indermuehle, Andreas; Timmis, Adam; Meier, Pascal (Current Cardiology Reviews, 2013)
Out-of-hospital cardiac arrest (OHCA) has attracted increasing attention over the past years because outcomes have improved impressively lately. The changes for neurological intact outcomes has been poor but several areas have achieved improving survival rates after adjusting their cardiac arrest care. The pre-hospital management is certainly key and decides whether a cardiac arrest patient can be brought back into a spontaneous circulation. However, the whole chain of resuscitation including the in-hospital care have improved also. This review describes aetiologies of OHCA, risk and potential protective factors and recent advances in the pre-hospital and in-hospital management of these patients.
Keywords: Out-of-hospital cardiac arrest